2019
DOI: 10.3390/inventions4030051
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Viscous Incompressible Bingham Fluid Flow through a Parallel Plate

Abstract: Numerical investigation for unsteady, viscous, incompressible Bingham fluid flow through parallel plates is studied. The upper plate drifts with a constant uniform velocity and the lower plate is stationary. Both plates are studied at different fixed temperatures. To obtain the dimensionless equations, the governing equations for this study have been transformed by usual transformations. The obtained dimensionless equations are solved numerically using the explicit finite difference method (FDM). The studio de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Some successful studies within a similar calculation framework can be found in Refs. [26][27][28][29][30][31].…”
Section: Calculation Techniquementioning
confidence: 99%
“…Some successful studies within a similar calculation framework can be found in Refs. [26][27][28][29][30][31].…”
Section: Calculation Techniquementioning
confidence: 99%
“…They also discussed the Bingham fluid flow in different cases, like, considering the laminar flow between two Riga (a combination of stable magnets and alternating electrodes) plates [16], considering oscillation on the upper plate of the porous channel [17]. Islam et al [18] studied the Bingham fluid through parallel plate, they didn't consider the magnetohydrodynamic (MHD) phenomena while in previous research the MHD phenomena are considered [14][15][16][17]. Now the question arises: What are the flow characteristics while the Bingham fluid is flowing through a porous parallel plate in the presence of Hall and Ion-slip current?…”
Section: Introductionmentioning
confidence: 99%